Quintuple helix model and urban development: a survey of strategic cooperation between university and industry - Hanafi, Nurhazliyana; Abdul Malek, Jalaluddin; Jusoh, Hamzah (2015)

(untitled)
A strong innovation ecosystem is important for the success of the urban development based on innovation and knowledge. The extent of strategic cooperation between universities and the industries affect economic, societal, and environmental balance. This article elaborates on the concept of generating innovation based on the Quintuple Helix Model and the knowledge city. The Quintuple Helix Model is based on the Triple Helix Model, to form innovation ecosystem through cooperation among universities, industries and the government. The Quadruple Helix Model is the addition of the fourth helix of the social and cultural context and while the fifth helix in the Quintuple Helix Model is the environment. The Triple Helix Model development is in line with the concept of developing a knowledge city consisting of the economic, social, and environmental aspects. The basis for this model and concept are innovation and knowledge. The main focus in driving development based on innovation and knowledge is to increase productivity and global competitiveness.